Flame-retardant polymer and cross-linked polyethylene composite and its use in photovoltaic cables
Patent Information
- Application Number
- CN202511318604.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-09-16
AI Technical Summary
Existing photovoltaic cable materials cannot simultaneously meet the requirements of high insulation, heat resistance, flame retardancy and mechanical properties. In particular, they are prone to aging under direct current and ultraviolet radiation. Furthermore, commonly used halogen-free flame retardants have poor compatibility with polyethylene matrix resins, resulting in decreased processability and mechanical properties.
A flame-retardant polymer containing polar groups and unsaturated bonds was designed and synthesized. It can undergo free radical polymerization with polyethylene main resin and has high compatibility with hydroxyl-containing inorganic fillers. By compounding with inorganic fillers such as nano-silica and nano-aluminum hydroxide, the flame-retardant and mechanical properties of cross-linked polyethylene composites can be improved.
The prepared cross-linked polyethylene composite material has higher mechanical properties, insulation and smoke suppression and flame retardancy at high temperatures, making it suitable for outdoor photovoltaic cables and reducing the risk of fire and the probability of electrical failure.
Smart Images

Figure CN121159859B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyolefin cable materials and their manufacturing, and specifically relates to a flame-retardant polymer and its preparation method and application, cross-linked polyethylene composite material and its preparation method, and its application in photovoltaic cables. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Currently, the most widely used polymer materials in wires and cables are polyvinyl chloride (PVC) and polyethylene (PE). Their applications mainly include bare wires, electrical equipment cables, power cables, communication cables and optical fibers, and winding wires. For outdoor solar photovoltaic cables, since photovoltaic power plants are typically designed for a lifespan of over 25 years, the cables, as critical components that are difficult to replace, require even higher environmental tolerance. Due to its chemical structure, PVC is prone to yellowing and aging degradation, especially under outdoor ultraviolet radiation, which can cause it to become brittle, crack, and powder. Therefore, polyethylene, with its better stability, is chosen as the main material for photovoltaic cables.
[0004] Polyethylene, with its linear or short-branched molecular chain structure, possesses good thermoplasticity and processability but poor mechanical properties. It is prone to significant deformation under long-term stress, leading to dimensional changes in the corresponding polymer products. To address the creep problem in polyethylene and improve its mechanical properties, cross-linking polyethylene can effectively suppress creep, increase its heat distortion temperature and resistance to environmental stress cracking, and enhance the long-term stability of the corresponding polymer products.
[0005] In addition, due to the application scenarios of photovoltaic cables, the requirements for the heat aging resistance of their cable materials are extremely high, as the temperature of photovoltaic systems under sunlight is maintained at 80-90℃ for extended periods. Furthermore, photovoltaic systems use direct current (DC), which is more prone to space charge accumulation and, compared to alternating current (AC), is more likely to generate electric arcs, thus requiring higher insulation performance from the cable materials. Simultaneously, when installed on or near buildings, photovoltaic cables are required to have good flame-retardant properties (low smoke, halogen-free) to reduce the risk of fire and the release of toxic fumes in a fire.
[0006] The requirements for cable materials in the photovoltaic cable application scenarios mentioned above are difficult for conventional cross-linked polyethylene to meet simultaneously. It is necessary to modify or fill it with other substances to form composite materials. However, the commonly used halogen-free flame retardants aluminum hydroxide or magnesium hydroxide have poor compatibility with polyethylene matrix resin and are difficult to disperse and fill evenly, resulting in a series of problems such as poor processability and reduced mechanical properties of cable materials. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the technical problem this invention aims to solve is to design and synthesize flame-retardant polymers that possess polar groups and contain unsaturated bonds capable of undergoing free radical polymerization with polyethylene matrix resins. Simultaneously, the flame-retardant polymer exhibits high compatibility with hydroxyl-containing inorganic fillers, improving the flame-retardant and mechanical properties of cross-linked polyethylene composites while meeting the requirements for high insulation and heat oxidation resistance.
[0008] Firstly, a flame-retardant polymer has the following general structural formula.
[0009] .
[0010] R1 is selected from hydrogen atoms or hydrocarbon groups with 1 to 6 carbon atoms. Preferably, the hydrocarbon group includes at least one double bond.
[0011] R2 is selected from hydrocarbon groups with 10-20 carbon atoms, wherein the hydrocarbon group includes at least one double bond.
[0012] R3 is selected from an aryl group with at least 6 carbon atoms, preferably R3 is selected from a phenyl group.
[0013] Secondly, the preparation method of the flame-retardant polymer described above includes: condensing bisphenol A or substituted bisphenol A with arylphosphoryl dichloro, and finally using cashew phenol for end capping.
[0014] Preferably, an acid-binding agent is used to neutralize the hydrochloric acid produced by the condensation reaction of bisphenol A or substituted bisphenol A with arylphosphoryl dichloro;
[0015] Preferably, an excess of bisphenol A or a substituted bisphenol A is first condensed with arylphosphoryl dichloro to obtain an intermediate product with phenolic groups at both ends, as shown below.
[0016] ;
[0017] The intermediate product is then subjected to a condensation reaction with the remaining arylphosphoryl dichloride, as shown below.
[0018] ;
[0019] Finally, cashew nut shell phenol is used for end capping, as shown below.
[0020] .
[0021] Preferably, the condensation reaction of excess bisphenol A or substituted bisphenol A with arylphosphoryl dichloro occurs at a temperature of 0°C to room temperature.
[0022] Preferably, the temperature for the condensation reaction of the intermediate product with the remaining arylphosphoryl dichloride and the cashew phenol end-capping is 60-90°C.
[0023] Preferably, the substituted bisphenol A is selected from 2,2'-diallyl bisphenol A (DBA).
[0024] Furthermore, the method for separating and purifying the flame-retardant polymer is as follows: after the reaction is completed, the reaction mixture is poured into water for extraction, the organic phase is filtered, the solvent is recovered by rotary evaporation, and the remaining product is dried under vacuum.
[0025] Thirdly, one application is the use of the flame-retardant polymers described above in polyolefin products.
[0026] Fourthly, a cross-linked polyethylene composite material includes: polyethylene resin, a free radical initiator, an antioxidant, an inorganic filler, and the flame-retardant polymer described above.
[0027] The polyethylene resin is selected from one or more combinations of low-density polyethylene, high-density polyethylene, and linear low-density polyethylene;
[0028] Preferably, the polyethylene resin is selected from one or more combinations of low-density polyethylene and linear low-density polyethylene.
[0029] The free radical initiator is selected from one or more of organic peroxides and azo initiators.
[0030] Preferably, the free radical initiator is selected from organic peroxides, which include one or more combinations of alkyl peroxides, hydroperoxides, acyl peroxides, and peroxycarbonates.
[0031] Further preferred, the free radical initiator is selected from alkyl peroxides;
[0032] Preferably, the free radical initiator is selected from one or a combination of two of di-tert-butyl peroxide and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
[0033] The antioxidants include a combination of free radical stabilizers and electron-donating antioxidants.
[0034] The free radical stabilizer is selected from hindered phenolic antioxidants. Preferably, the free radical stabilizer is selected from: 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-ethylphenol, 2,4-dimethyl-6-tert-butylphenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 4,4'-bis(2,6-di-tert-butylphenol), 4,4'-bis(2-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl- The following are any one or more combinations of 6-tert-butylphenol, 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 4,4'-isopropylidenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-methylenebis(4-methyl-6-nonylphenol), 2,2'-isobutylidenebis(4,6-dimethylphenol), 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2,6-bis(2'-hydroxy-3'-tert-butyl-5'-methylbenzyl)-4-methylphenol.
[0035] Among them, electron-donating antioxidants are selected from one or more of amide, sulfoxide and phosphite antioxidants;
[0036] Preferably, the electron-donating antioxidant is selected from phosphite antioxidants;
[0037] Further preferred, the electron-donating antioxidant is selected from one or a combination of two of tris(2,4-di-tert-butyl)phosphite and tris(nonylphenyl)phosphite.
[0038] The inorganic filler is selected from one or more combinations of hydroxyl-containing silicon-based fillers and metal hydroxides. The surface of the inorganic filler contains hydroxyl groups to provide active sites, which can bind to the flame-retardant polymer through intermolecular forces, enhance the compatibility between the filler and the matrix resin, and improve the mechanical properties of the composite material.
[0039] Preferably, the hydroxyl-containing silicon-based filler is selected from one or more combinations of amorphous silica, nano silica, kaolin, montmorillonite, and talc.
[0040] The metal hydroxide is selected from one or more combinations of aluminum hydroxide and magnesium hydroxide.
[0041] Furthermore, the cross-linked polyethylene composite material also includes a cross-linking agent containing at least two vinyl groups, which is capable of free radical polymerization with polyethylene resin and flame-retardant polymer, thereby participating in the cross-linking curing reaction.
[0042] Preferably, the crosslinking agent is selected from one or more combinations of tetramethyltetravinylcyclotetrasiloxane, triallyl isocyanurate, trimethylolpropane diallyl ether, triallyl pentaerythritol, and triallyl cyanurate.
[0043] Furthermore, the cross-linked polyethylene composite material is prepared from the following raw materials in parts by weight: 90-110 parts polyethylene resin, 0.1-1.0 parts free radical initiator, 0.1-1.0 parts antioxidant, 1-10 parts inorganic filler, and 5-15 parts flame retardant polymer.
[0044] Preferably, the cross-linked polyethylene composite material is prepared from the following raw materials in parts by weight: 90-110 parts polyethylene resin, 0.1-1.0 parts free radical initiator, 0.1-1.0 parts antioxidant, 1-10 parts inorganic filler, 5-15 parts flame retardant polymer, and 0.1-2 parts cross-linking agent.
[0045] Fifthly, the preparation method of the cross-linked polyethylene composite material described above includes: pre-mixing inorganic fillers with flame-retardant polymers, mixing the resulting mixture with other components in the formulation, and then melting, extruding, cooling, and pelletizing the mixture to obtain the cross-linked polyethylene composite material.
[0046] Preferably, the inorganic filler and flame-retardant polymer are premixed for 10-60 minutes;
[0047] Preferably, the mixture obtained by premixing the inorganic filler and the flame-retardant polymer is mixed with other components in the formulation for 10-60 minutes.
[0048] Preferably, a screw extruder is used to melt and extrude the mixture, with the extruder temperature set to 180-230°C and the residence time to 30-120 seconds.
[0049] Sixthly, one application is the use of the cross-linked polyethylene composite material described above in photovoltaic cables.
[0050] The beneficial effects of this invention are as follows: A flame-retardant polymer with bisphenol A or its derivatives and aryl phosphoryl groups as its core is designed and synthesized. Both ends of the polymer are capped with cashew phenol containing long-chain hydrocarbon groups. The unsaturated bonds of these long-chain hydrocarbon groups can react with polyethylene resin or a crosslinking agent under the action of a free radical initiator. The resulting crosslinked polyethylene composite material exhibits higher mechanical properties, heat resistance, insulation, and smoke suppression and flame retardancy. Simultaneously, the flame-retardant polymer itself possesses polar groups, exhibiting high compatibility with hydroxyl-containing inorganic fillers. By compounding it with inorganic fillers such as nano-silica and nano-aluminum hydroxide, the maximum operating temperature, insulation protection effect, and flame retardancy of the crosslinked polyethylene composite material are further improved, reducing the requirements for short-circuit and overload protection in photovoltaic cables, making it more suitable for outdoor photovoltaic cable materials. Attached Figure Description
[0051] Figure 1 Thermogravimetric (TG) curves and thermogravimetric differential (DTG) curves of the flame-retardant polymer prepared in Example 1.
[0052] Figure 2 The infrared spectra of intermediate product 1-1 and final product 1-2 prepared in Example 1 are shown. Detailed Implementation
[0053] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0054] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0055] Unless otherwise specified, the experimental conditions used in the examples are generally in accordance with conventional conditions in the art or the conditions recommended by the reagent company. Unless otherwise specified, the materials and reagents used in the examples can be purchased commercially.
[0056] Example 1
[0057] 50.22 g (0.22 mol) of bisphenol A (BPA), 46 g of triethylamine and 20 mL of acetonitrile were added to a flask. The reaction system temperature was lowered to 10 °C by an ice bath with stirring. Then, 19.5 g (0.1 mol) of phenylphosphodichlorophenyl chloride was added to the flask. The flask temperature was maintained at 10-20 °C and the reaction was carried out for 4 hours to obtain product 1-1.
[0058] Product 1-1:
[0059]
[0060] Characterization of product 1-1, 1 ¹H-NMR (400 MHz, solvent DMSO-d6): δ 1.78 (12H, s, -CH3), 6.89 (2H, m, -OH), 7.03 (11H, m, Ar-H), 7.56 (2H, t, Ar-H), 7.99 (8H, m, Ar-H).
[0061] Based on product 1-1, 46.8 g (0.24 mol) of phenylphosphodichloro and 50 mL of acetonitrile were added for chain extension. The temperature was raised to 80 °C and a condenser was inserted for reflux reaction for 8 hours. Then, 15.02 g (0.05 mol) of cardol (Cardolite® NX-2026) was added as a capping agent and the reaction was continued for 6 hours, and finally the reaction was terminated.
[0062] After the reaction was completed, the reaction mixture was poured into 300 mL of ice water, separated, the aqueous phase was extracted with dichloromethane, the organic phases were combined, the organic phase was washed once with saturated brine, and then the organic phase was filtered. The filtrate was collected and the solvent was recovered by rotary evaporation. The remaining residual product was dried under vacuum at 70 °C for 12 hours to obtain a brown powder, which is the flame retardant polymer, with the corresponding structures being products 1-2.
[0063] Thermogravimetric analysis (TGA) was performed on the flame-retardant polymers, resulting in thermogravimetric (TG) curves and thermogravimetric differential (DTG) curves, which are listed below. Figure 1 middle.
[0064] The final product 1-2 and intermediate product 1-1 were analyzed by infrared spectroscopy (KBr pellet method), and the results are as follows: Figure 2 As shown. For Figure 2 Infrared spectroscopy analysis revealed that intermediate product 1-1 was present at 3310 cm⁻¹. -1 (phenolic hydroxyl group), 3105 cm -1 (Ar-H), 2843cm -1 (-CH2), 1203 cm -1 (PO) and 1170cm -1(POC), thus confirming the introduction of the phosphoryl group into the molecular backbone, products 1-2 at 2850 cm⁻¹ -1 With 1660cm -1 The significantly enhanced absorption in the vicinity indicates the introduction of long-chain hydrocarbon groups through cashew phenol end capping, and that these hydrocarbon groups contain unsaturated alkenyl groups.
[0065] Product 1-2:
[0066]
[0067] Example 2
[0068] 67.85 g (0.22 mol) of 2,2'-diallylbisphenol A (DBA), 25 mL of triethylamine, and 20 mL of acetonitrile were added to a flask. The reaction system temperature was lowered to 10 °C with stirring and an ice bath. Then, 19.5 g (0.1 mol) of phenylphosphine dichloride was added to the flask, and the reaction was carried out at 10-20 °C for 4 hours to obtain product 2-1.
[0069] Product 2-1:
[0070]
[0071] Characterization of product 2-1, 1H-NMR (400 MHz, solvent DMSO-d6): δ 1.66 (12H, s, -CH3), 3.38 (8H, d, Ar-CH2-CH=CH2), 5.10-5.21 (8H, m, -CH=CH2), 5.90-6.07 (4H, m, Ar-CH2-CH=CH2), 6.87 (2H, m, Ar-OH), 7.05-7.24 (11H, m, Ar-H), 7.57 (2H, t, Ar-H), 7.94-8.11 (8H, m, Ar-H).
[0072] Based on product 2-1, 46.8 g (0.24 mol) of phenylphosphodichloro and 50 mL of acetonitrile were added for chain extension. The temperature was raised to 80 °C and a condenser was inserted for reflux reaction for 8 hours. Then, 15.02 g (0.05 mol) of cardol (Cardolite® NX-2026) was added as a capping agent and the reaction was continued for 6 hours, and finally the reaction was terminated.
[0073] After the reaction was completed, the reaction mixture was poured into 300 mL of ice water, separated, the aqueous phase was extracted with dichloromethane, the organic phases were combined, the organic phase was washed once with saturated brine, and then the organic phase was filtered. The filtrate was collected and the solvent was recovered by rotary evaporation. The remaining product was dried under vacuum at 70 °C for 12 hours to obtain a brown powder, which is the flame retardant polymer, with the corresponding structure being product 2-2.
[0074] Product 2-2:
[0075]
[0076] Example 3
[0077] By weight, 15 parts of linear low-density polyethylene (Yanshan Petrochemical LD100BW, melt index 2.0 g / 10 min, 190℃, 2.16 kg, the same applies below), 85 parts of low-density polyethylene (Yanshan Petrochemical LD200GH, melt index 2.1 g / 10 min, melt index 2.0 g / 10 min, 190℃, 2.16 kg, the same applies below), 0.5 parts of free radical initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 0.2 parts of free radical stabilizer antioxidant 101 were added. 0 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, hereinafter abbreviated as Antioxidant 1010], 0.1 parts of electron-donating antioxidant tris(2,4-di-tert-butyl) phenyl phosphite, 0.1 parts of electron-donating antioxidant tris(nonylphenyl) phosphite, 3 parts of hydrophilic fumed silica nano-silica HL200 (Hubei Huifu Nanomaterials), 9.5 parts of the flame-retardant polymer prepared in Example 1, 0.4 parts of crosslinking agent trimethylolpropane diallyl ether, and 0.8 parts of crosslinking agent triallyl pentaerythritol.
[0078] The flame-retardant polymer was first premixed with the inorganic filler hydrophilic fumed silica for 15 minutes, and then the above components were mixed according to the formula ratio for 30 minutes. The mixture was then added to a twin-screw extruder for melting. The extruder temperature was 200℃ and the residence time was 90 seconds. The extruded product was cooled in a circulating water bath and pelletized to obtain a cross-linked polyethylene composite material.
[0079] Example 4
[0080] By weight, 15 parts linear low-density polyethylene, 85 parts low-density polyethylene, 0.5 parts free radical initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.2 parts free radical stabilizer antioxidant 1010, 0.1 parts electron-donating antioxidant tris(2,4-di-tert-butyl)phosphite, 0.1 parts electron-donating antioxidant tris(nonylphenyl)phosphite, 2.5 parts hydrophilic fumed silica nano-silica HL200, 0.5 parts nano aluminum hydroxide ZH-AlOH-01 (Zhonghang Nano), 11 parts flame-retardant polymer prepared in Example 1, 0.4 parts crosslinking agent trimethylolpropane diallyl ether, and 0.8 parts crosslinking agent triallyl cyanurate.
[0081] The flame-retardant polymer was first premixed with inorganic fillers, hydrophilic fumed silica and nano-alumina hydroxide, for 15 min. Then, the above components were mixed according to the formulation ratio for 30 min. Subsequently, the mixture was added to a twin-screw extruder for melting. The extruder temperature was 200℃ and the residence time was 90 s. The extruded product was cooled in a circulating water bath and pelletized to obtain a cross-linked polyethylene composite material.
[0082] Example 5
[0083] By weight, 15 parts linear low-density polyethylene, 85 parts low-density polyethylene, 0.5 parts free radical initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.2 parts free radical stabilizer antioxidant 1010, 0.1 parts electron-donating antioxidant tris(2,4-di-tert-butyl)phosphite, 0.1 parts electron-donating antioxidant tris(nonylphenyl)phosphite, 3 parts hydrophilic fumed silica nano-silica HL200, 8 parts flame-retardant polymer prepared in Example 2, and 0.5 parts crosslinking agent trimethylolpropane diallyl ether.
[0084] The flame-retardant polymer was first premixed with the inorganic filler hydrophilic fumed silica for 15 minutes, and then the above components were mixed according to the formula ratio for 30 minutes. The mixture was then added to a twin-screw extruder for melting. The extruder temperature was 200℃ and the residence time was 90 seconds. The extruded product was cooled in a circulating water bath and pelletized to obtain a cross-linked polyethylene composite material.
[0085] Example 6
[0086] By weight, 15 parts linear low-density polyethylene, 85 parts low-density polyethylene, 0.5 parts free radical initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.2 parts free radical stabilizer antioxidant 1010, 0.1 parts electron-donating antioxidant tris(2,4-di-tert-butyl)phosphite, 0.1 parts electron-donating antioxidant tris(nonylphenyl)phosphite, 2.5 parts hydrophilic fumed silica nano-silica HL200, 0.5 parts nano aluminum hydroxide ZH-AlOH-01, 12 parts flame-retardant polymer prepared in Example 2, and 0.5 parts crosslinking agent trimethylolpropane diallyl ether.
[0087] The flame-retardant polymer was first premixed with inorganic fillers, hydrophilic fumed silica and nano-alumina hydroxide, for 15 min. Then, the above components were mixed according to the formulation ratio for 30 min. Subsequently, the mixture was added to a twin-screw extruder for melting. The extruder temperature was 200℃ and the residence time was 90 s. The extruded product was cooled in a circulating water bath and pelletized to obtain a cross-linked polyethylene composite material.
[0088] Comparative Example 1
[0089] By weight, the following components are used: 15 parts linear low-density polyethylene, 85 parts low-density polyethylene, 0.5 parts free radical initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.2 parts free radical stabilizer antioxidant 1010, 0.1 parts electron-donating antioxidant tris(2,4-di-tert-butyl)phosphite, 0.1 parts electron-donating antioxidant tris(nonylphenyl)phosphite, 2.5 parts hydrophilic fumed silica nano-silica HL200, 0.5 parts nano aluminum hydroxide ZH-AlOH-01, 0.4 parts crosslinking agent trimethylolpropane diallyl ether, and 0.8 parts crosslinking agent triallyl pentaerythritol.
[0090] The above components were mixed according to the formula ratio, and then the mixture was added to a twin-screw extruder for melting. The extruder temperature was 200℃, the residence time was 90s, and the extruded product was cooled in a circulating water bath and pelletized to obtain a cross-linked polyethylene composite material.
[0091] Comparative Example 2
[0092] By weight, 15 parts linear low-density polyethylene, 85 parts low-density polyethylene, 0.5 parts free radical initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.2 parts free radical stabilizer antioxidant 1010, 0.1 parts electron-donating antioxidant tris(2,4-di-tert-butyl)phosphite, 0.1 parts electron-donating antioxidant tris(nonylphenyl)phosphite, 10.5 parts flame-retardant polymer prepared in Example 1, 0.4 parts crosslinking agent trimethylolpropane diallyl ether, and 0.8 parts crosslinking agent triallyl pentaerythritol.
[0093] The above components were mixed according to the formula ratio, and then the mixture was added to a twin-screw extruder for melting. The extruder temperature was 200℃, the residence time was 90s, and the extruded product was cooled in a circulating water bath and pelletized to obtain a cross-linked polyethylene composite material.
[0094] Performance testing section
[0095] Flame retardant properties: The smoke density of cross-linked polyethylene composites was determined by the single-chamber method in Part II of GB / T 8323.2; the limiting oxygen index of cross-linked polyethylene composites was determined by GB / T 2406.
[0096] Mechanical properties and anti-aging properties: The tensile properties, elongation at break and impact resistance of cross-linked polyethylene composites were tested according to the standards of JB / T 10437 and GB / T 1043.1. At the same time, the cross-linked polyethylene composites were subjected to a hot air oxidation test (hot air oxidation conditions 170℃*300h) according to the standard of GB / T 2951.12. After oxidation, the tensile properties, elongation at break and impact resistance were tested again.
[0097] Electrical properties:
[0098] Volume resistivity: Refer to GB / T 1410 standard, use a high resistance meter to measure the volume resistivity of the sample. The sample size is 100×100×1mm, and a three-electrode test system is used.
[0099] Breakdown field strength: Refer to the standard GB / T 1408. The breakdown voltage of the sample is tested by a breakdown voltage tester. The sample size is 100×100×1mm and the electrode is a circular electrode with a diameter of 25mm.
[0100] The test results of Examples 3-6 and Comparative Examples 1-2 are listed in Tables 1 and 2.
[0101] Table 1
[0102] Table 2
[0103] Analysis of the results in Tables 1 and 2 shows that Examples 3-6 used the flame-retardant polymers prepared in Examples 1-2. By adding cashew phenol as a capping agent and introducing unsaturated double bonds using diallyl bisphenol A, cross-linked polyethylene composites were prepared through cross-linking reactions between unsaturated bonds under the action of an initiator. This introduced phenylphosphine oxide flame retardants. Furthermore, the combination with inorganic fillers containing hydroxyl groups (such as nano-silica) or inorganic flame retardants (such as nano-aluminum hydroxide) can improve heat resistance to oxidation, insulation properties, and flame retardancy and smoke suppression effects. This is because the hydroxyl groups on the surface of the inorganic fillers can form hydrogen bonds with the P=0 and ether bonds in the flame-retardant polymer, thereby improving compatibility with the cross-linked polyethylene system. Inorganic fillers such as silica can form a silica layer during combustion, which, together with the char layer, acts as a heat insulation and oxygen barrier, thus producing a synergistic effect and improving the flame retardancy of the cross-linked polyethylene composite. In addition, inorganic fillers such as silica have better insulation properties, which can improve the volume resistivity and breakdown field strength of the composite material.
[0104] Comparative Example 1 did not use the flame-retardant polymer prepared in Examples 1 or 2. It relied solely on inorganic filler nano-aluminum hydroxide as a flame retardant. The compatibility between aluminum hydroxide and the cross-linked polyethylene system is generally poor, and its flame-retardant and smoke-suppressing effects are relatively worse than those in Examples 3-6. Moreover, the addition of inorganic fillers such as silica and aluminum hydroxide leads to a decrease in the mechanical properties of the composite material, and the high-temperature oxidation resistance is also relatively low.
[0105] Comparative Example 2 used the flame-retardant polymer prepared in Example 1, but did not use inorganic fillers. Lacking inorganic fillers such as silica to hybridize with organic resin through hydrogen bonding, the flame-retardant and smoke-suppressing effects of the cross-linked polyethylene composite material in Comparative Example 2 were relatively low, while its insulation and heat oxidation resistance were significantly lower than those of the cross-linked polyethylene composite materials in Examples 3-6.
[0106] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A cross-linked polyethylene composite material, characterized in that, Composite materials include: polyethylene resin, free radical initiators, antioxidants, crosslinking agents, inorganic fillers, and flame-retardant polymers; The polyethylene resin is selected from one or more combinations of low-density polyethylene, high-density polyethylene, and linear low-density polyethylene; The free radical initiator is selected from one or more of organic peroxides and azo initiators; The inorganic filler is selected from one or more combinations of hydroxyl-containing silicon-based fillers and metal hydroxides; The crosslinking agent contains at least two vinyl groups and is capable of free radical polymerization with polyethylene resin and flame-retardant polymers, thereby participating in the crosslinking and curing reaction; The flame-retardant polymer is obtained by condensation reaction of bisphenol A or substituted bisphenol A with arylphosphoryl dichloro, and finally end-capped with cashew phenol. The cross-linked polyethylene composite material is prepared from the following raw materials in parts by weight: 90-110 parts polyethylene resin, 0.1-1.0 parts free radical initiator, 0.1-1.0 parts antioxidant, 1-10 parts inorganic filler, and 5-15 parts flame retardant polymer.
2. The cross-linked polyethylene composite material according to claim 1, characterized in that, The method for separating and purifying the flame-retardant polymer is as follows: after the reaction is completed, the reaction mixture is poured into water for extraction, the organic phase is filtered, the solvent is recovered by rotary evaporation, and the remaining product is dried under vacuum.
3. The cross-linked polyethylene composite material according to claim 1, characterized in that, The acid-binding agent is used to neutralize the hydrochloric acid produced by the condensation reaction of bisphenol A or substituted bisphenol A with arylphosphoryl dichloro.
4. The cross-linked polyethylene composite material according to claim 1, characterized in that, First, excess bisphenol A or substituted bisphenol A is condensed with arylphosphoryl dichloro to obtain an intermediate product with phenolic groups at both ends, as shown below. ; The intermediate product is then subjected to a condensation reaction with the remaining arylphosphoryl dichloride, as shown below. ; Finally, cashew nut shell phenol is used for end capping, as shown below. ; R1 is selected from hydrogen atoms or hydrocarbon groups with 1 to 6 carbon atoms; R2 is selected from hydrocarbon groups with 10 to 20 carbon atoms, wherein the hydrocarbon group includes at least one double bond; R3 is selected from aryl groups with at least 6 carbon atoms.
5. The cross-linked polyethylene composite material according to claim 4, characterized in that, The condensation reaction of excess bisphenol A or substituted bisphenol A with arylphosphoryl dichloro occurs at temperatures ranging from 0°C to room temperature.
6. The cross-linked polyethylene composite material according to claim 4, characterized in that, The intermediate product undergoes a condensation reaction with the remaining arylphosphoryl dichloride, and the cashew phenol is capped at a temperature of 60-90℃.
7. The cross-linked polyethylene composite material according to claim 1, characterized in that, The substituted bisphenol A is selected from 2,2'-diallyl bisphenol A.
8. The cross-linked polyethylene composite material according to claim 1, characterized in that, The polyethylene resin is selected from low-density polyethylene and linear low-density polyethylene.
9. The cross-linked polyethylene composite material according to claim 1, characterized in that, The free radical initiator is selected from organic peroxides, which include one or more combinations of alkyl peroxides, hydroperoxides, acyl peroxides, and peroxycarbonates.
10. The cross-linked polyethylene composite material according to claim 1, characterized in that, The free radical stabilizer is selected from: 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-ethylphenol, 2,4-dimethyl-6-tert-butylphenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 4,4'-bis(2-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), and 4,4'-butylbis(3-methyl-6-tert-butylphenol). Any one or more combinations of 4,4'-isopropylidene bis(2,6-di-tert-butylphenol), 2,2'-methylene bis(4-methyl-6-cyclohexylphenol), 2,2'-methylene bis(4-methyl-6-nonylphenol), 2,2'-isobutylidene bis(4,6-dimethylphenol), 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2,6-bis(2'-hydroxy-3'-tert-butyl-5'-methylbenzyl)-4-methylphenol.
11. The cross-linked polyethylene composite material according to claim 1, characterized in that, The antioxidant is selected from phosphite antioxidants.
12. The cross-linked polyethylene composite material according to claim 1, characterized in that, The hydroxyl-containing silicon-based filler is selected from one or more combinations of amorphous silica, kaolin, montmorillonite, and talc.
13. The cross-linked polyethylene composite material according to claim 1, characterized in that, The metal hydroxide is selected from one or more combinations of aluminum hydroxide and magnesium hydroxide.
14. The cross-linked polyethylene composite material according to claim 1, characterized in that, The crosslinking agent is selected from one or more combinations of tetramethyltetravinylcyclotetrasiloxane, triallyl isocyanurate, trimethylolpropane diallyl ether, triallyl pentaerythritol, and triallyl cyanurate.
15. A method for preparing a cross-linked polyethylene composite material according to any one of claims 1-14, comprising: Inorganic fillers and flame-retardant polymers are premixed, and the resulting mixture is mixed with other components in the formulation. The mixture is then melted, extruded, cooled, and pelletized to obtain a cross-linked polyethylene composite material.
16. An application characterized in that, The application of the cross-linked polyethylene composite material as described in any one of claims 1-14 in photovoltaic cables.
Citation Information
Patent Citations
Preparation method of efficient flame-retardant modified unsaturated polyester resin
CN113429770A
Halogen-free low-smoke insulating material for B1-grade flame-retardant cable and preparation method of halogen-free low-smoke insulating material
CN113527775A
High-performance cross-linked polyolefin cable material and preparation method thereof
CN118515927A
